Level of Vitamin A in beef steer rations: Wintering phase - Richardson, D.; Smith, E.F.; Dunn, L.; Harbers, L.H. (Kansas Agricultural Experiment Station, 2011)
Sixty Hereford steer calves were divided into six equal lots. Sorghum silage ad lib. And 1 pound of soybean oil meal per head daily were fed to all lots. Half of the animals (Lots 7, 8, and 9) received 8 pounds of sorghum grain pr head daily; the other half (Lots 10, 11, and 12), 4 pounds per head daily. This phase of the test was to measure performance on two levels of grain and prepare the animals for the fattening phase. At the beginning of the fattening phase, the animals were reallotted to six lots of 10 with five animals from the 8-pound level of grain and five from the 4-pound level.
Keywords: Beef; Vitamin A; Performance; Gain